2023
DOI: 10.17829/turcom.1122465
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Migrants’ Perceptions of Turkish and Iranian Culture: A Comparative Analysis with ZMET Technique

Abstract: The aim of this study is to determine the perceptions of culture and communication in the social life of Iran and Turkey. In the study, the prominent aspects, which Iranian migrants experience the culture and communication in social life, were examined. Also, the most prominent issues in Turkish and Iranian culture for Iranian immigrants were tried to be determined. In this context, Iranian immigrants living in Turkey were reached by using snowball sampling, and Zaltman’s ZMET Technique is used in the study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…showed that these migrants associated Iranian culture with diverse elements such as the Nowruz festival, family, Iranian dishes and desserts, historical symbols, and religious symbols. By contrast, when discussing Turkish culture, the migrants emphasized features such as Atatürk, the Turkish flag, family, the city, and social life (Batu et al, 2023). To capture ethnic symbols embedded in place (i.e., in China), this study relied on ZMET and participant observations to gain relevant information from children.…”
Section: Methodsmentioning
confidence: 99%
“…showed that these migrants associated Iranian culture with diverse elements such as the Nowruz festival, family, Iranian dishes and desserts, historical symbols, and religious symbols. By contrast, when discussing Turkish culture, the migrants emphasized features such as Atatürk, the Turkish flag, family, the city, and social life (Batu et al, 2023). To capture ethnic symbols embedded in place (i.e., in China), this study relied on ZMET and participant observations to gain relevant information from children.…”
Section: Methodsmentioning
confidence: 99%